Ünlü Türk Mantıkçısı Ebheri ve Mantık Kuralları Risalesi - el-Ebheri, Esirüddin Mufaddal b. Ömer es-Semerkandi (İlim Yayma Cemiyeti, 2001)
Athar al-Din al-Abhari is an important figure whose works had been textbooks in the Ottoman schools for centuries al-Abhari who wrote so many books in such areas as philosophy, mathematics, astronomy and logic is especially known for his books Hidayat al-Hikmat and İsaghuji He took logic into account in all of his works of philosophy. He also wrote some books and treatises specially concerning logical problems. Here, we are going to present the Turkish translation of his al-Risâlah fi al-Kavaid al-Mantıqiyyah (The Treatise in The Logical Rules)
The Eminent Turkish Logician al-Abhari and "al-Risalah fi al-Kavaid al-Mantıqiyyah"
Keywords: al-Abhari; Ebherî; Sarıoğlu; Philosophy; Logic; Isaghuji; Kavaid